Konstruksi Tokoh Margio dalam Novel berjudul Lelaki Harimau karya Eka Kurniawan - Ellif Shiffiyn Khairaa (BASIS (Bahasa dan Sastra Inggris), 2020)
This researched aims to analyze the characterization of Margio as the main character of the novel entitled Lelaki Harimau by Eka Kurniawan. This study used narrative structure by Gerard Genette which focused on frequency concept to analyze the characterization. The descriptive qualitative method used to reveal and make a deep analysis of the characterization of Margio. The data is taken by reread the novel and written the quotations of the dialogue which focused on the characterization of Margio. The result of this study is Margio has strong characterization and he is the one who connected to the other characters in the novel. He is known as a lovable, obedient to their parents, and a strong man. The moral value of this novel is the key to a perfect family is the good communication of each member of the family. This study is important in how we learned the complexity of human relations, especially in the family.